IMPACT OF GREEN SUPPLY CHAIN MANAGEMENT ON ORGANIZATIONAL PERFORMANCE - KAZIM RIAZ; DR. MUHAMMAD ASIM; SALMAN MANZOOR (CenRaPS Journal of Social Sciences, 2020)
This study evaluated the relation of implementing the green supply chain management on the entire business performance. This research has been done on the organizations in the e-commerce industry based in Karachi, Pakistan. The research has found that there is a direct relationship between green supply chain management, which includes the variables, Cooperation with Suppliers, Green Purchasing, Green Logistics, And Cooperation with Customers and the organizational performance. The results showed that business performance grows if the green supply chain management enhances operational efﬁciency and operational efﬁciency. The study has found and that the implementation of the sustainable supply chain in the firm has a positive impact on the economic performance of the company and competitiveness, hence provide a competitive edge to the company. This study also provides a clear image of how important the green chain plays a part in the organizational performance and that is for the well-being of the employees.